2016
DOI: 10.4103/0971-5916.198679
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance & pathogen profile in ventilator-associated pneumonia in a tertiary care hospital in India

Abstract: Background & objectives:Ventilator-associated pneumonia (VAP) is an important hospital-acquired infection with substantial mortality. Only a few studies are available from India addressing the microbiological aspects of VAP, which have been done with small study populations. This study was carried out in the intensive care units (ICUs) of a tertiary care hospital to assess the profile of pathogens and to determine the pattern of antimicrobial resistance.Methods:This was a retrospective study of clinically susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Similarly, in an Indian study, the most frequent microorganisms isolated from VAP patients were, in order, Klebsiella spp. and P. aeruginosa [27]. Additionally, previous studies in India and the same geographical country of our study Egypt on VAP reported Klebsiella spp.…”
Section: Discussionsupporting
confidence: 66%
“…Similarly, in an Indian study, the most frequent microorganisms isolated from VAP patients were, in order, Klebsiella spp. and P. aeruginosa [27]. Additionally, previous studies in India and the same geographical country of our study Egypt on VAP reported Klebsiella spp.…”
Section: Discussionsupporting
confidence: 66%
“…First, the authors have raised the appropriateness of including Candida as a pathogen for ventilator associated pneumonia (VAP), since it is extremely rare and lung biopsy is the only definitive method for diagnosis of Candida pneumonia. Earlier, the data from 24 investigations conducted with ventilated patients for a total of 1,689 episodes and 2,490 pathogens revealed Candida as an aetiological agent in 0.9 per cent 2 while in our study, it was 2.0 per cent (63 out of 3084 clinically suspected cases) 3 which may not be termed substantially high. We agree that the existing bronchoscopic or non-bronchoscopic specimens are not appropriate for diagnosis of Candida pneumonia and Candida recovered from such samples signifies colonization.…”
contrasting
confidence: 54%
“…10 In critical ill patients, the longer period of mechanical ventilation and hospital stay increases colonization rate and the incidence of resistant bacteria. 14 15 In a study from North India, Mehndiratta, et al have reported isolates of Pseudomonas, Klebsiella and E. coli with 100% sensitivity to imipenem and all the gram-positive isolates studied were sensitive to linezolid. 16 In this study,the most effective antibiotic against gram negative bacilli was found to be Imipenem followed by Piperacillin tazobactam.…”
Section: Discussionmentioning
confidence: 99%